Success of Handmade Transobturator Slings Prepared From Conventional Polypropylene Mesh in the Treatment of Stress Urinary Incontinence in Women (Bangladesh Journal of Urology, 2020)
Objective: To determine the improvement of the quality of life in patient of BPH after transurethral resection of prostate.Methods: A total of 102 of patients complaining lower urinary tract symtoms due to Benign prostatic hyperplasia (BPH). Each of the patient was followed up at 8 weeks (1st visit), 16 weeks (2nd visit) and 24 weeks (3rd visit) after transurethral resection of prostate (TURP). Before TURP for base line study of each patient was evaluated by history, physical examination, digital rectal examination (DRE), International Prostate Symptoms Score (IPSS), Quality of Life Score (QOL), Urinalysis, volume of the prostate and post voidal residual urine (PVR) were determined by ultrasonogram. Improvement of lower urinary tract symptoms and quality of life was determined using IPSS. Improvement was based on the changes from base line in symptoms,urinary flow rate, amount of post voidal residual urine and quality of life.Urine flow rate was measured by uroflowmetry as peak urinary flow rate (Qmax), voiding time and voided volume and was considered valid only if the voided volume was >200 ml. Symptoms were assessed using IPSS & consisting of seven symptoms (frequency, nocturia, urge in continence, urgency, hesitancy, terminal dribbling and sense of incomplete evacuation) that were graded from 0-5. An overall symptoms score was calculated.Result: 102 cases were evaluated by history, physical examination, digital rectal examination (DRE), international prostate symptom scoring (IPSS), quality of life (QOL) scoring, uroflowmetry, post voided residual urine (PVR) and volume of prostate by USG and serum prostate specific antigen (PSA). Cases were selected between 60-75 years. In group-A, among 42 cases (41.2%) 65 years. Age of the patients of each group was compared with IPSS, PVR, Qmax and QOL. Before TURP, IPSS range 17-25 and mean 21.61+2.43, after TURP, range 0-7 and mean 4.27+1.71). There was significant correlation between the IPSS obstructive scores and Qmax at base line (P=